A comparison of programmed cell death between species. - Tittel, J.N.; Steller, H. (Genome Biology, 2000)
Key components of the programmed cell death pathway are conserved between Caenorhabditis elegans, Drosophila melanogaster and humans. The search for additional homologs has been facilitated by the availability of the entire genomic sequence for each of these organisms.